2017
DOI: 10.1051/0004-6361/201731121
|View full text |Cite
|
Sign up to set email alerts
|

NH3(10–00) in the pre-stellar core L1544

Abstract: Pre-stellar cores represent the initial conditions in the process of star and planet formation, therefore it is important to study their physical and chemical structure. Because of their volatility, nitrogen-bearing molecules are key to study the dense and cold gas present in pre-stellar cores. The NH 3 rotational transition detected with Herschel-HIFI provides a unique combination of sensitivity and spectral resolution to further investigate physical and chemical processes in pre-stellar cores. Here we presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 52 publications
5
41
2
Order By: Relevance
“…It is also consistent with the kinetic temperature derived with non-LTE modelling for methanol towards the L1544 dust peak by Vastel et al (2014) (7-15 K). This result confirms that CH 3 OH is mainly tracing a shell around the L1544 dust peak, as towards the centre, Crapsi et al (2007) found temperatures of ∼6 K using NH 3 , which does not appear to freeze-out (see also Caselli et al 2017). The opposing directions of the methanol and ammonia temperature gradients further support the notion that the methanol gradient is only an excitation effect caused by changes in the gas density.…”
Section: Rotational Temperaturesupporting
confidence: 74%
“…It is also consistent with the kinetic temperature derived with non-LTE modelling for methanol towards the L1544 dust peak by Vastel et al (2014) (7-15 K). This result confirms that CH 3 OH is mainly tracing a shell around the L1544 dust peak, as towards the centre, Crapsi et al (2007) found temperatures of ∼6 K using NH 3 , which does not appear to freeze-out (see also Caselli et al 2017). The opposing directions of the methanol and ammonia temperature gradients further support the notion that the methanol gradient is only an excitation effect caused by changes in the gas density.…”
Section: Rotational Temperaturesupporting
confidence: 74%
“…Radiative transfer simulations of the ortho-ammonia (1 0 − 0 0 ) line. The simulated lines correspond to the Herschel observations ofCaselli et al (2017), shown in black. The ammonia abundance profiles are taken from model CM1 (blue; see text) or model CM2 (red).…”
mentioning
confidence: 87%
“…Second, we took the physical structure from K10 and mapped the ammonia abundance profile from Crapsi et al (2007) onto this physical model, i.e., both models use the same parametrization for the ammonia abundance. The beam FWHM and spectral resolution were set to 40 ′′ and 64 m s −1 , respectively, corresponding to the Herschel observations of Caselli et al (2017). The results of this comparison are shown in Fig.…”
Section: Ammonia Line Emission Simulationsmentioning
confidence: 99%
“…However, for the core centre, the modelled abundance is much lower than the observed value. Recently, Caselli et al (2017) also found that their chemical model predicts a much lower abundance in the central part of L1544 and they concluded that several factors might play an important role in this discrepancy, such as the underestimation of the production of gas phase NH 3 . The observed upper limits of NH 2 CHO in L1544 (≤2.4-6.7×10 −13 ; Jiménez-Serra et al 2016) agree well with our predictions for the estimated age of the core.…”
Section: Nh 2 Chomentioning
confidence: 99%